Penerapan Pola Asuh Authoritative Sebagai Upaya Pencegahan Kenakalan Remaja Di Desa Warukaranganyar - Rahayu, Tyas Wilantari; Arsal, Thriwaty (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
Teenagers often experience upheaval within themselves so that they fall into juvenile delinquency. Parents need to define the type of parenting that suits the characteristics of adolescents. Determining the appropriate parenting style can have an impact on preventing juvenile delinquency. The application of authoritative (democratic) parenting is a form of effort by parents in Warukarangnyar village as a form of preventing juvenile delinquency against children. The objective of this research is to examine applying authoritative parenting in families to children as an effort to prevent juvenile delinquency in Warukaranganyar village. This research applies a type of descriptive qualitative approach to make appropriate interpretations of findings in the field. Data collection techniques are sourced from observational data, interviews, and documentation. Parental samples were taken by purposive sampling of 7 people. The results of the study showed of authoritative parenting applied by parents in Warukaranganyar village through the application of rules, recognition of children, maintaining smooth communication and giving rewards and punishments. Meanwhile, the obstacles that occur in implementing authoritative parenting in Warukaranganyar village include internal and external obstacles.